2020
DOI: 10.1002/ece3.6474
|View full text |Cite
|
Sign up to set email alerts
|

Tree litter functional diversity and nitrogen concentration enhance litter decomposition via changes in earthworm communities

Abstract: Biodiversity is a major driver of numerous ecosystem functions. However, consequences of changes in forest biodiversity remain difficult to predict because of limited knowledge about how tree diversity influences ecosystem functions. Litter decomposition is a key process affecting nutrient cycling, productivity, and carbon storage and can be influenced by plant biodiversity. Leaf litter species composition, environmental conditions, and the detritivore community are main components of the decomposition process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…In contrast with C mic and M loss , the abundance of microarthropods was not affected by litter diversity (Table 3). Some previous studies found mixtures to promote the abundance of microarthropods (Hansen, 2000; Hättenschwiler & Gasser, 2005; Migge et al., 1998; Schädler & Brandl, 2005), while others did not find evidence that litter diversity beneficially affects microarthropods (Bluhm et al., 2019; Ilieva‐Makulec et al., 2006; Korboulewsky et al., 2016; Patoine et al., 2020; Scheu et al., 2003). Our results agree with the latter findings and support the results of Marian et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with C mic and M loss , the abundance of microarthropods was not affected by litter diversity (Table 3). Some previous studies found mixtures to promote the abundance of microarthropods (Hansen, 2000; Hättenschwiler & Gasser, 2005; Migge et al., 1998; Schädler & Brandl, 2005), while others did not find evidence that litter diversity beneficially affects microarthropods (Bluhm et al., 2019; Ilieva‐Makulec et al., 2006; Korboulewsky et al., 2016; Patoine et al., 2020; Scheu et al., 2003). Our results agree with the latter findings and support the results of Marian et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) suggesting that litter diversity in this tropical rainforest neither improves habitat conditions nor the availability of resources for microarthropods, at least during early stages of decomposition. Indeed, detritivore microarthropods are considered to comprise predominantly generalist feeders colonizing a range of forest types and therefore are rather insensitive to changes caused by litter mixing (Ball et al., 2014; Gergócs & Hufnagel, 2016; Patoine et al., 2020; Wardle et al., 2006). However, even though litter diversity did not affect microarthropod abundance, it may still have fostered the diversity of microarthropods, as has been shown for other soil organisms, such as testate amoebae at our study site (Krashevska et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In overall, the average similarity index during observations on the three sites is low, below 50% (21% to 35%). The behavior of macrofauna in food preferences during sufficient amount of litter is a factor causing the high similarity index at the beginning of the observation [42]. Meanwhile, the similarity index decreases in line with the decrease in the amount of litter.…”
Section: Similarity Indexmentioning
confidence: 96%
“…Third, the spatial distribution of soil resources may also partly explain our observations. A weak but positive tree diversity effect on abundance and diversity of earthworms was observed across the FunDivEUROPE plots (De Wandeler et al, 2018), indicating an increased bioturbation and redistribution of soil nutrients in mixtures (Meysman et al, 2006;Patoine et al, 2020). As a response, trees could have formed higher-SRL roots to enhance their chance of encountering nutrient-rich spots .…”
Section: Accepted Articlementioning
confidence: 98%